Effects of urbanization, industrialization, economic growth, energy consumption, financial development on carbon emissions: An extended STIRPAT model for heterogeneous income groups - Muhammad Tariq Majeed; Aisha Tauqir (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
This study examines the effects of urbanization and industrialization on carbon emissions for a panel of 156 countries and various income groups over the period 1990-2014 employing the first and second-generation tests. To address the issues of heterogeneity, endogeneity, and cross-sectional dependence,dynamic generalization method of moments (GMM), common correlated effects mean group (CCEMG) and dynamic CCEMG estimation procedures are applied. Carbon emissions, urbanization, industrialization, economic growth, financial development, and energy consumption are integrated of order one. The results show that urbanization and industrialization have statistically positive and significant effects on carbon emissions across all panel groups. Whereas economic growth exerts heterogeneous effects on environmental pollution, validating the implications of "environmental Kuznets curve". Similarly, financial development raises pollution in all income groups except high-income countries. The findings did not confirm "theory of ecological urbanization" while the evidence on "ecological modernization theory" is inconclusive. Overall findings imply that the global challenge of environmental pollution is mainly aggravated by rapid urbanization and industrialization whereas economic growth, financial development, and energy consumption have heterogeneous effects depending upon the development stage of countries. This study recommends that sustainable urbanization and industrialization need to be promoted using green finance and clean energy sources.
Keywords: 330; environment; climate change; greenhouse gases; industrial growth; urbanization; CO2 emissions; energy consumption; financial development; GDP